Mewujudkan kebun lorong kota yang estetika dan produktif melalui tanaman hidroponik di Kelurahan Ujung Pandang Baru Kota Makassar - Marhawati Marhawati; Agus Syam; Ismail Ismail (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The "city alley" Community Partnership Program in the Ujung Pandang Baru village of Makassar City is based on the fact that the field : 1) Structuring the aisles in Makassar City has become a city government program, but it is only limited to piloting and prioritizing its aesthetic value, very limited with economically valuable plants, such as vegetables. Meanwhile, the aisles as an example are fully facilitated by the city government. Potted plants and other supporting facilities such as compost have been prepared, and 2) Specifically for Ujung Pandang Baru Village, Makassar City, only 5 of the 80 active Park aisles. other aisles are not active and / or are not included in the sample aisles.This is because the garden aisle program is more top-down without the active participation of the community. For this reason, in the context of learning and community empowerment, it needs to be educated so that they can manage the plants and fertilizers used for plant fertility.The method of implementation of this activity is training and technical assistance in the cultivation of the hydroponic system because it is following the conditions of the alley which no longer leaves land for direct planting. Meanwhile, to support the growth of plants, both vegetables and ornamental plants, environmentally friendly fertilizer in the form of liquid organic fertilizer (POC) and / or compost using the Takakura method is needed. All stages of the activity are carried out in a participatory manner involving the target group. This PKM activity has given changes to the aspects of knowledge and skills of participants in cultivating hydroponic system plants, especially the variety of healthy vegetables and of economic value, skilled in making environmentally friendly liquid organic fertilizers.